Demokrasi dalam Sejarah Ketatanegaraan Republik Indonesia - Wijaya, Arif (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract; this paper highlights democracy in the history of the constitution of the Republic of Indonesia. In the history of the nation, from independence to now, there are three kinds of democracy that once applied in the constitutional life of Indonesia, namely the liberal democracy, the guided democracy, and the Pancasila democracy. The liberal democracy leads to a failure of the Constituent establishing Undang-Undang Dasar 1945 as a replacement of Undang-Undang Dasar Sementara 1950. The Guided Democracy is under the reign of the old order and the Pancasila democracy is under the rule of the new order. Although the initial concept for the period intended as an implementation of the fourth principle of Pancasila, but the power was ultimately centralized on the hand of President. A failure of the old and the new order to uphold the values of democracy cause a reformation. In this reformation era, the values of democracy are expected to be enforced.Keywords: The liberal democracy, the guided democracy, the Pancasila democracy